2021
DOI: 10.7717/peerj.11837
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic individuality in the hissing calls of the male black grouse (Lyrurus tetrix)

Abstract: Acoustic individuality may well play a big role during the mating season of many birds. Black grouse (Lyrurus tetrix) produces two different long-distance calls during mating on leks: rookooing and hissing calls. The first one represents low frequency series of bubbling sounds and the second one represents hissing sound. This hissing represents a signal not produced by the syrinx. We analyzed 426 hissing calls from 24 individuals in Finland and Scotland. We conducted cross-validated discrimination analyses (DF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The hisses of P. valeriae lack a temporal organization, such as those vocalizations composed of repeated notes at regular intervals emitted by different Gekkota members, e.g., [32][33][34]. On the other hand, the hisses of P. valeriae showed high aggregate entropy (high disorder), almost twice that of the values recorded for the vocalizations and hisses of other vertebrates, e.g., Sirenia, Galliformes and Anura [35][36][37], including the vocalizations of the lizard Aspidoscelis costatus costatus [9]. In addition, these hisses covered a wide frequency range, from 0.9 kHz to >20 kHz.…”
Section: Discussionmentioning
confidence: 89%
“…The hisses of P. valeriae lack a temporal organization, such as those vocalizations composed of repeated notes at regular intervals emitted by different Gekkota members, e.g., [32][33][34]. On the other hand, the hisses of P. valeriae showed high aggregate entropy (high disorder), almost twice that of the values recorded for the vocalizations and hisses of other vertebrates, e.g., Sirenia, Galliformes and Anura [35][36][37], including the vocalizations of the lizard Aspidoscelis costatus costatus [9]. In addition, these hisses covered a wide frequency range, from 0.9 kHz to >20 kHz.…”
Section: Discussionmentioning
confidence: 89%
“…These signals are an important part of courtship on leks because both males and females decide which lek to visit based on acoustic performance [52]. Recently, it was found that the grouse's non-vocal hissing calls carry an individual specificity that makes it possible to distinguish individuals from each other [53].…”
Section: Introductionmentioning
confidence: 99%